SAT0358 Impact of Methotrexate on Anti-TNF Treatment in Psoriatic Arthritis? an In-Depth Analysis of A Large Prospective Observational Study with Adalimumab. (10th June 2014) - Behrens, F.; Köhm, M.; Arndt, U.; Wittig, B.; Greger, G.; Thaci, D.; Scharbatke, E.; Tony, H.-P.; Burkhardt, H.
Abstract : Background: In active psoriatic arthritis (PsA) the efficacy of TNF-inhibitors (TNFi) has been proven in randomized clinical trials (RCT). Methotrexate (MTX) co-medication can improve the therapeutic benefit of TNFi in rheumatoid arthritis (RA), but its role in PsA remains unclear. Thus, distinct patterns of disease manifestations such as peripheral joint and axial involvement might influence the choice of co-medication, treatment response and drug adherence differently in PsA. Accordingly, an appropriate study on the impact of MTX on TNFi treatment in PsA has to consider the confounding effects of the distinct disease manifestations on outcome measures. Methods: Data of a large German multicentre, prospective observational study (n=1455) with active PsA patients treated with Adalimumab (ADA) in routine care was analysed. Patients were stratified in a cohort with exclusive peripheral arthritis (pPsA) i.e. no evidence for axial involvement, enthesitis and dactylitis and in a group with additional musculoskeletal manifestations (aPsA) for separate analysis. Safety and efficacy of ADA-monotherapy were analysed and compared to the results obtained by add-on treatment to MTX pre-medication. Besides documentation of demographic data, disease activity assessments (number of swollen (SJC), tender joints (TJC), disease activity score 28 (DAS28)) were calculated at baseline, month 3, 6, 12, 24. Treatment adherence (no withdrawal) and reasons for withdrawal were documented. In addition, those patients who stopped MTX after combinational treatment and those who added MTX (in ADA-monotherapy) were analysed. Step-wise regression analysis for influence of MTX on patient-outcome was calculated. Results: DAS28 values after 24 months of ADA treatment is independent from concomitant MTX use in both groups (pPsA: ADA+MTX 2.58, ADA-Monotherapy 2.70; aPsA: ADA+MTX 2.82, ADA-Monotherapy 2.79 respectively). Treatment adherence was comparable in both groups as well as withdrawal rates due to lack of efficacy or adverse events. Moreover, treatment responses remained robust to changes of MTX co-medication either by discontinuation in combined TNFi therapy or by addition to TNFi-monotherapy. In step-wise regression analysis no parameters for MTX were found to influence patient-outcome. Conclusions: In both, axial and peripheral involvement of PsA, co-medication of MTX added to TNFi treatment with ADA has no relevant impact on efficacy, safety or treatment adherence. Not even the addition of MTX to ongoing TNFi treatment or termination of MTX in combinational therapy with TNFi exhibits any influence on outcome. RCTs are needed to confirm the data. Disclosure of Interest: F. Behrens Grant/research support: Abbvie Deutschland GmbH & Co.KG, M. Köhm Grant/research support: Abbvie Deutschland GmbH & Co.KG, U. Arndt: None declared, B. Wittig Employee of: Abbvie Deutschland GmbH & Co.KG, G. Greger Employee of: Abbvie Deutschland GmbH & Co.KG, D. Thaci Grant/research support: Abbvie Deutschland GmbH & Co.KG, E. Scharbatke Grant/research support: Abbvie Deutschland GmbH & Co.KG, H.-P. Tony Grant/research support: Abbvie Deutschland GmbH & Co.KG, H. Burkhardt Grant/research support: Abbvie Deutschland GmbH & Co.KG DOI: 10.1136/annrheumdis-2014-eular.1225